A MULTIDIMENSIONAL FRAMEWORK FOR PSYCHOMOTOR REHABILITATION AND INCLUSIVE EDUCATION IN CHILDREN WITH CEREBRAL PALSY (UKLO Proceedings, 2026)
This research used an interdisciplinary model that integrates psychomotor rehabilitation with inclusive education for students with cerebral palsy. The research revealed the need for individualized, specific rehabilitation that supports functional independence and active participation in learning environments. A case study design was used including a nine-year-old girl with spastic diplegic cerebral palsy attending a regular school. Standardized instruments such as the Gross motor function classification system, Manual ability classification system, Modified Ashworth scale, and Pediatric evaluation of disability inventory were used. Cognitive, communicative, social and emotional functioning were assessed through classroom observations, evaluations, and interviews. The results showed moderate motor limitations and dysarthric speech but preserved visual perception, motivation, and symbolic understanding. Environmental and systemic barriers such as fragmented rehabilitation services and insufficient interprofessional collaboration limited her progress. The results clarify the relevance of coordinated, family-centered intervention integrating rehabilitation, education, and social support to improve inclusion and general development in children with cerebral palsy.